Procedurally generating surface detail for 3D models using voxel-based cellular automata - Mazzolini, Ryan (Department of Computer Science, 2016)
Procedural generation is used extensively in the field of computer graphics to automate content generation and speed up development. One particular area often automated is the generation of additional colour and structural detail for existing 3D models. This empowers artists by providing a tool-set that enhances their existing work-ow and saves time. 3D surface structures are traditionally represented by polygon mesh-based models augmented by 2D mapping techniques. These methods can approximate features, such as caves and overhangs, however they are complex and difficult to modify. As an alternative, a grid of voxels can model 3D shapes and surfaces, similar to how 2D pixels form an image. The regular form of voxel-based models is easier to alter, at the cost of additional computational overhead. One technique for generating and altering voxel content is by using Cellular Automata (CA). CAs are able to produce complex structures from simple rules and also easily map to higher dimensions, such as voxel datasets. However, creating CA rule-sets can be difficult and tedious. This is especially true when creating multidimensional CA. In our work we use a grammar system to create surface detail CA. The grammar we develop is similar to formal grammars used in procedural generation, such as L-systems and shape grammars. Our system is composed of three main sections: a model converter, grammar and CA executor. The model converter changes polygon-mesh models to and from a voxel-based model. The grammar provides a simple language to create CA that can consider 3D neighbourhoods and query parameters, such as colour or structure. Finally, the CA executor interprets the produced grammars into surface-oriented CAs. The final output of this system is a polygon-mesh model, altered by the CA, which is usable for graphics applications. We test the system by replicating a number of CA use-cases with our grammar system. From the results, we conclude that our grammar system is capable of creating a wide range of 3D detail CA. However, the high resolution of resulting meshes and slow processing times make the process more suited to o_-line processing and pre-production.